Penerapan Islamic Worldview dalam Pembelajaran di MI Muhammadiyah Ngasem - Mujadid, Kasori; Dewi, Rachma Rusdiana (Lembaga Yasin AlSys, 2025)
Character education has an important role in forming individuals who are not only intellectually intelligent, but also have noble character. Islamic Religious Education (PAI) has a strategic role in developing the character of students, by integrating Islamic values ​​in all aspects of life. One of the approaches used is the application of the Islamic Worldview, which includes the Islamic perspective on God, humans, the universe, and relationships between people. This article discusses the application of the Islamic Worldview in learning at MI Muhammadiyah Ngasem, which aims to shape the character of students who are superior both academically and spiritually. This research uses a qualitative approach with a case study at MI Muhammadiyah Ngasem, which involves observation, interviews and document analysis. The research results show that the application of Islamic Worldview through the integration of Islamic values ​​in the curriculum, moral education, balanced self-development, and Islamic extracurricular activities has a positive impact on increasing noble morals, empathy, social awareness, responsibility in learning, as well as increasing cooperation and tolerance. . However, there are challenges related to educators' understanding of the Islamic Worldview concept, difficulties in integrating Islamic values ​​in the existing curriculum, lack of student readiness and parental involvement in the learning process, difficulties in implementing contextual education, as well as limited learning facilities and resources.